2003
DOI: 10.1080/00015550310007427
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 in Normal Sun-exposed and Protected Skin (Type IV-V) in Different Decades of Age

Abstract: The checkpoint protein p53, which is activated by DNA damage, is involved in the decision whether the cells should stop replication and proceed to repair their DNA or die by apoptosis. We evaluate the expression of p53 and the number of apoptotic cells in normal sun-exposed (face) and protected (abdomen) skin in Egyptians between 6 and 77 years of age. The degree of p53 expression in facial skin significantly increases from a score of 1.5 +/- 1.5 (mean +/- SEM) in the 1st decade to 4.8 +/- 0.3 in the 8th decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…p53 accumulation in a dispersed pattern has been reported in chronically sun-exposed skin 13,14 and was found to increase in an age-dependent pattern that may reflect a cumulative insult to DNA of epidermal cells. 14 It has been also noted that such accumulation of p53 in photoaged skin is partially related to altered keratinocyte differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…p53 accumulation in a dispersed pattern has been reported in chronically sun-exposed skin 13,14 and was found to increase in an age-dependent pattern that may reflect a cumulative insult to DNA of epidermal cells. 14 It has been also noted that such accumulation of p53 in photoaged skin is partially related to altered keratinocyte differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown increased p53 expression in chronically sun-exposed skin [5,36] and with aging [37], so it is not surprising that there is a link between these two histological features. Furthermore, in the same Nambour population, we have shown that p53 immunoreactivity in the epidermis was also a marker of ultraviolet exposure during the past 6 months [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, significantly higher p53 expression has been reported in sun-exposed and photo-aged skin as a result of sun-induced DNA damage. [1819]…”
Section: Introductionmentioning
confidence: 99%